EFFECTIVENESS OF GRATITUDE INTERVENTIONS IN SCHOOLS TO INCREASE SENSE OF SCHOOL BELONGING TO HIGH SCHOOL STUDENTS - Fadil, Ahmad; Ayriza, Yulia (International Journal of Social Service and Research, 2024)
A sense of school belonging that tends to be low has an impact on problematic behavior at school, so effective psychological intervention is needed. One form of intervention carried out is gratitude intervention. This study aims to determine the effectiveness of gratitude interventions in increasing the sense of school belonging of high school students. This study uses a quantitative approach with the type of experimental research, and the design used is a pre-experimental one group pretest-posttest design. The research was conducted on students of SMA Negeri 5 Soppeng with 34 students. The determination of research participants was using the purposive sampling technique. Data were obtained by filling out the Psychological Sense of School Membership (PSSM) scale before and after the gratitude intervention. The validity of the PSSM scale was calculated using the Aiken's V test and obtained a coefficient of 0.88, while the reliability test used Cronbach's Alfa, with a reliability coefficient value of 0.86. The data analysis technique uses the N-Gain score test. The results showed that the average score of sense of school belonging before the intervention was 40.15, while after the intervention it increased to 73.5, the results of the hypothesis test using the difference index (N Gain Score) recorded an increase of 55.9. Thus, the hypothesis in this study is accepted, which means that gratitude interventions in schools are quite effective in increasing the sense of school belonging of high school students.